Implementasi Kebijakan Kesehatan di Era Modern: Analisis Bibliometrik terhadap Dinamika Keberlanjutan Layanan Kesehatan Tradisional di Tengah Persaingan dengan Sistem Kesehatan Modern - A. Pananrangi M (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to analyze the implementation of health policies in the modern era by highlighting the sustainability dynamics of traditional health services amidst the dominance of modern healthcare systems. Using a bibliometric approach, this study explores scientific publications indexed in the Scopus database over the period 2019–2024. The analysis focuses on publication trends, dominant keywords, institutional collaborations, and country contributions related to the integration of traditional health services into national health policies. The findings reveal a significant increase in publications discussing integrative approaches, particularly concerning the formal recognition and potential of traditional services in supporting sustainable healthcare systems. Nevertheless, challenges such as regulatory inconsistencies, limited funding, and scientific validation continue to pose major barriers. This study recommends the formulation of more inclusive and adaptive health policies that accommodate diverse medical systems while prioritizing the effectiveness, safety, and accountability of healthcare delivery.